2014
DOI: 10.1186/2045-9912-4-11
|View full text |Cite
|
Sign up to set email alerts
|

Expression analysis following argon treatment in an in vivo model of transient middle cerebral artery occlusion in rats

Abstract: BackgroundArgon treatment following experimental neurotrauma has been found neuroprotective in an array of in vivo and in vitro models. The inherent cellular and molecular mechanisms are still unknown. We seeked to shed light on these processes by examinig the cellular distribution and the expression of inflammatory markers and growth factors in argon treated brain tissue.MethodsMale adult Sprague-Dawley rats were randomly assigned to one of the study groups: sham surgery + placebo, sham surgery + argon, tMCAO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 35 publications
(50 reference statements)
1
40
0
1
Order By: Relevance
“…In 2014, Fahlenkamp et al [24] performed 2 h of tMCAO in rats. After one hour of tMCAO, animals received argon (50% argon, 50% O 2 ) or placebo (50% N 2 , 50% O 2 ) for the next tMCAO hour via face mask.…”
Section: Argon As a Neuroprotective Gaseous Molecule In Various Momentioning
confidence: 99%
“…In 2014, Fahlenkamp et al [24] performed 2 h of tMCAO in rats. After one hour of tMCAO, animals received argon (50% argon, 50% O 2 ) or placebo (50% N 2 , 50% O 2 ) for the next tMCAO hour via face mask.…”
Section: Argon As a Neuroprotective Gaseous Molecule In Various Momentioning
confidence: 99%
“…Hence, we investigated the mRNA levels of representative genes which, especially in the first few hours after hepatectomy (“priming phase”), are of particular importance [2,21]. Additionally, a connection to the previously proven effects of argon on these genes should exist [8,13]. …”
Section: Resultsmentioning
confidence: 99%
“…In an experiment on rats, it was found that 24 h after transient middle cerebral artery occlusion there was a significant increase in IL-6 and TNF in the penumbra following 1 h of 50 vol% argon inhalation in comparison to a group with nitrogen inhalation [13]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rodent models of cardiac arrest followed by cardiopulmonary resuscitation have exhibited improved neurological performance and decreased neuronal damage with argon postconditioning [7,8,9]. Argon postconditioning was also neuroprotective in stroke models (middle cerebral artery occlusion) [10,11] and in vitro models of cerebral ischaemia and traumatic brain injury [12,13,14]. In vitro studies using organotypic cultures or tumour cells have demonstrated that argon treatment also protects against ultraviolet irradiation [15] and cytotoxic agents [16,17].…”
Section: Introductionmentioning
confidence: 99%